2001
DOI: 10.1074/jbc.m010064200
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Synthase Elevation in Metastatic Prostate Carcinoma Cells Correlates with Hyaluronan Surface Retention, a Prerequisite for Rapid Adhesion to Bone Marrow Endothelial Cells

Abstract: Bone marrow is the primary site of metastasis in patients with advanced stage prostate cancer. Prostate carcinoma cells metastasizing to bone must initially adhere to endothelial cells in the bone marrow sinusoids. In this report, we have modeled that interaction in vitro using two bone marrow endothelial cell (BMEC) lines and four prostate adenocarcinoma cell lines to investigate the adhesion mechanism. Highly metastatic PC3 and PC3M-LN4 cells were found to adhere rapidly and specifically (70 -90%) to BMEC-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
97
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 67 publications
7
97
0
2
Order By: Relevance
“…1 Highly metastatic PC3M-LN4 cells (1) were found to adhere rapidly to human bone marrow-derived sinusoidal endothelial cell lines, whereas poorly metastatic LNCaP cells were only weakly adherent (2). This adhesion, specific for BMECs relative to other endothelial cells, was subsequently found to depend upon the presence of a pericellular hyaluronan (HA) matrix assembled on the PC3M-LN4 cells.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…1 Highly metastatic PC3M-LN4 cells (1) were found to adhere rapidly to human bone marrow-derived sinusoidal endothelial cell lines, whereas poorly metastatic LNCaP cells were only weakly adherent (2). This adhesion, specific for BMECs relative to other endothelial cells, was subsequently found to depend upon the presence of a pericellular hyaluronan (HA) matrix assembled on the PC3M-LN4 cells.…”
mentioning
confidence: 96%
“…In our previous report, we determined that HAS2 and HAS3, normally present at low levels in the prostate, are strongly up-regulated in metastatic prostate tumor cells (2). In this report, we have used the in vitro BMEC adhesion model to examine the role of these enzymes and their product in prostate cancer bone metastasis.…”
mentioning
confidence: 99%
“…For example, the rate of HA synthesis is enormously increased when oncogenic viruses transform fibroblasts (7,8), and elevated levels of HA are associated with the hyperproliferative and malignant phenotypes in melanomas and various carcinomas (9)(10)(11).…”
Section: H Yaluronan (Ha) Is a Linear Polysaccharide Composed Of A Rementioning
confidence: 99%
“…2,3 Such interactions of tumor pericellular hyaluronan may contribute to "seeding" or initial survival of tumor cells during early stages of metastasis to bone or other organs. A similar conclusion was reached in another study in which inhibition of mammary tumor cell interaction with hyaluronan led to their rapid apoptosis within hours of entry into the lung interstitium.…”
Section: Hyaluronan In Tumor Cell Growth and Survivalmentioning
confidence: 99%
“…In previous studies, these investigators showed that aggressive PC3M-LN4 human prostate carcinoma cells contain two of the three synthases that synthesize hyaluronan, namely HAS2 and HAS3, and that transfectants of PC3M-LN4 with antisense to HAS2 and HAS3 mRNA synthesized significantly less hyaluronan. 2,3 In the present study, stable transfectants with antisense-HAS2 and antisense-HAS3 were used alone or in combination to study tumor growth after subcutaneous injection in immunocompromised mice. The antisense-HAS transfectants produced tumors that were three to four times smaller than control tumors after 3 weeks.…”
mentioning
confidence: 99%